Economics of research and innovation in agriculture - Moser, Petra (National Bureau of Economic Research conference report., 2021)
"The challenges facing agriculture are plenty. Along with the world's growing population and diminishing amounts of water and arable land, the gradual increase in severe weather presents new challenges and imperatives for producing new, more resilient crops to feed a more crowded planet in the twenty-first century. Innovation has historically helped agriculture keep pace with earth's social, population, and ecological changes. In the last 50 years, mechanical, biological, and chemical innovations have more than doubled agricultural output while barely changing input quantities. The ample investment behind these innovations was available because of a high rate of return: a 2007 paper found that the median ROI in agriculture was 45 percent between 1965 and 2005. This landscape has changed. Today many of the world's wealthier countries have scaled back their share of GDP devoted to agricultural R&D amid evidence of diminishing returns. Universities, which have historically been a major source of agricultural innovation, increasingly depend on funding from industry rather than government to fund their research. As Upton Sinclair wrote of the effects industry influences, "It is difficult to get a man to understand something when his salary depends upon his not understanding it." In this volume of the NBER Conference Report series, editor Petra Moser offers an empirical, applied-economic framework to the different elements of agricultural R&D, particularly as they relate to the shift from public to private funding. Individual chapters examine the sources of agricultural knowledge and investigate challenges for measuring the returns to the adoption of new agricultural technologies, examine knowledge spillovers from universities to agricultural innovation, and explore interactions between university engagement and scientific productivity. Additional analysis of agricultural venture capital point to it as an emerging and future source of resource in this essential domain"--